Applications of Gene Editing in Chickens: A New Era Is on the Horizon - Sid, Hicham; Schusser, Benjamin (Frontiers in Genetics, 2018)
The chicken represents a valuable model for research in the area of immunology, infectious diseases as well as developmental biology. Although it was the first livestock species to have its genome sequenced, there was no reverse genetic technology available to help understanding specific gene functions. Recently, homologous recombination was used to knockout the chicken immunoglobulin genes. Subsequent studies using immunoglobulin knockout birds helped to understand different aspects related to B cell development and antibody production. Furthermore, the latest advances in the field of genome editing including the CRISPR/Cas9 system allowed the introduction of site specific gene modifications in various animal species. Thus, it may provide a powerful tool for the generation of genetically modified chickens carrying resistance for certain pathogens. This was previously demonstrated by targeting the Trp38 region which was shown to be effective in the control of avian leukosis virus in chicken DF-1 cells. Herein we review the current and future prospects of gene editing and how it possibly contributes to the development of resistant chickens against infectious diseases.